Postgraduate orthopaedics : MCQS and EMQS for the FRCS (Tr & Orth) - Sri-Ram, Kesavan (Cambridge : Cambridge University Press, 2012)
"What do you need to do before sitting the written component of the FRCS (Tr and Orth) examination? Practice, practice, practice. Sadly the MCQs and EMQs in the actual examination are not this straightforward. This book will help the orthopaedic surgeon preparing for the written part of the examination to be ready to face the task ahead. The MCQs and EMQs appear in the same format as the examination and cover the syllabus topics. Divided into subspecialty chapters, including trauma and basic science, this book is ideal for use alongside a revision plan. The questions have detailed answers and selected references, arming readers with the knowledge they need to approach the topic correctly. Written by recent, successful examination candidates, this question-and-answer-based revision guide is ideal preparation for the FRCS (Tr and Orth) examination as well as being helpful for other postgraduate orthopaedic exams"--Provided by publisher.
Machine generated contents note: Preface; Foreword Barry Ferris; 1. Introduction Kesavan Sri-Ram; 2. Hand and wrist Maxim Horwitz and Elliot Sorene; 3. Shoulder and elbow Deborah Higgs and Simon Lambert; 4. Spine Zaher Dannawi and Rajiv Bajekal; 5. Hip and pelvis Nashat Siddiqui and Phil Kerr; 6. Knee Kesavan Sri-Ram and Howard Ware; 7. Foot and ankle Kesavan Sri-Ram and Andrew Robinson; 8. Pathology Danyal Nawabi and Tim Briggs; 9. Paediatric orthopaedics Russell Hawkins and Deborah Eastwood; 10. Trauma Paul Whittingham-Jones, Kesavan Sri-Ram and Dennis Edwards; 11. Basic science Ben Rudge and John Skinner; Index.
Includes bibliographical references and index.
Keywords: Orthopedic Procedures; Examination Questions